Modular approach for modeling cell motility - Ziebert, Falko; Aranson, Igor S. (European physical journal special topics, 2014)
Modeling cell movement is a challenging task since the motility machinery is highly complex. Moreover, there is a rather broad diversity of different cell types. In order to obtain insights into generic features of the motility mechanisms of several distinct cell types, we propose a modular approach that starts with a minimal model, consisting of a phase field description of the moving cell boundary and a simplified internal dynamics. We discuss how this starting point can be extended to increase the level of detail, and how the internal dynamics “module” can be changed/adjusted to properly model various cell types. The former route allows studying specific processes involved in cell motility in the framework of a self-organized moving domain, and the latter might permit to put different cellular motility mechanisms into a unified framework.